(untitled) (Research, Society and Development, 2022)
Objective: To know the impact of the covid-19 pandemic on the management of nursing services. Method: A qualitative research will be developed. Qualitative research is concerned with the reality that cannot be quantified, working with beliefs, values ​​and attitudes, which make up a deeper space of relationships. Qualitative research works with the universe of meanings, motives, aspirations, beliefs, values ​​and attitudes, which corresponds to a deeper space of relationships, processes and phenomena that cannot be reduced to the operationalization of variables (MINAYO, 2007). The present project was developed with nurses working in two medium-sized hospitals located in the Northwest of the state of Rio Grande do Sul, Hospital Divina Providência and Hospital Santo Antônio, located, respectively, in the municipalities of Frederico Westphalen and Tenente Portela. The study will be carried out with professional nurses working in sectors that are directly linked to the screening, treatment or rehabilitation of patients who have or have had a diagnosis of covid-19, namely: covid ICU, adult ICU, hospitalization, emergency and surgical center sectors.Two professionals from each sector will participate in the study, 10 participants from each of the hospitals, totaling 20 participants. Results: With the development of this project, it was possible to understand the management of nursing services, which was classified into three categories (1) Organization of services health during the pandemic; (2) Challenges encountered in the management of nursing services; (3) From the new managerial perspectives arising from the pandemic. Conclusion: With the research, it can be observed that there were several managerial demands of nursing, which had to adapt and reinvent itself in order to provide assistance with the increase in cases and complexities. The pandemic exposed the need for greater investments in the health area, with better working conditions and the need for health services to be trained for pandemic situations, such as the one that emerged with covid-19.